Pleistocene paleoenvironmental evolution at continental middle latitude inferred from carbon and oxygen stable isotope analysis of ostracodes from the Guadix-Baza Basin (Granada, SE Spain) - Torres Pérez-Hidalgo, Trinidad José (E.T.S.I. Minas (UPM), 2006)
A representative paleoenvironmental reconstruction of continental middle latitude from ca. 2my to the upper part of Middle Pleistocene (279±77ky) was obtained from the carbon and oxygen stable isotopes analyzed in ostracode shells (Cyprideis torosa) recovered in the Guadix-Baza Basin (SE Spain), an intramontaneous closed depression filled by alluvial and lacustrine sediments. This study was performed along a 356-m-thick composite section, dated previously by paleomagnetism and the amino acid racemization method. 013C and 0180 profiles reflected changes in temperature, the evaporationJinfill ratio in the water bodies and the amount of rain. 013C is also affected by changes in plant biomass: periods with high 013C and 0180 values are associated with warm and dry regimes, and with less vegetation, which, in some cases, coincide with the development of displacive gypsum crystals, whereas low 013C and 0180 values correlate with cold and humid episodes, which cause more vegetation biomass and, therefore, increasing the input of isotopically light carbon. Intermediate 0180 values are linked to temperate dry or humid episodes when they coincide with high or low 013C values, respectively. 86 paleoclimatic events were distinguished in the Pleistocene record from the 013C and 0180 profiles. From both the statistical analysis of the geochemical data and the geological observations, four Cold and Humid Long Periods (low 0180) and four Warm and Dry Long Periods (high 0180) were defined. This differs with respect to the paleoclimatological behavior established for the Northern Hemisphere where during cold periods (glacial), no water was available while permafrost conditions persisted, whereas in warm episodes (interglacial), higher precipitation rates occurred. Good correspondences between the Guadix-Baza Basin paleoclimatic record and a marine oxygen-isotope sequence, two continental cores and other long Mediterranean paleoenvironmental records (pollen sequences from Israel) were found, which suggested that climate changes in ...